Frontline Pakistan : The Path to Catastrophe and the Killing of Benazir Bhutto - Zahid Hussain (India Penguin Books, 2008)
After the assassination of Benazir Bhutto, Pakistan stands on the edge of an abyss into which it may plunge the world. As this nuclear power nation, the front line of the West s struggle against Al Qaeda, enters the worst political crisis in its history, Zahid Hussain s acclaimed and updated book unravels the key questions: who really controls the country? Will Pakistan be Talibanized? Has Al Qaeda infiltrated the state? After 9/11, Pakistan s controversial President, Pervez Musharraf stunned the world by announcing his support for America s War on Terror . But in Pakistan, as Zahid Hussain reveals, nothing is as it seems. The author documents for the first time in detail the incestuous relationship between Pakistan s jihadis and its all-powerful military intelligence agency the ISI. He penetrates the jihadi networks, revealing their sources of funding, and their links with the Taliban and Al Qaeda, and based on exclusive interviews with key players, he shows us the fall-out from Musharraf s momentous decision to support America. From the dangerous mountain passes of Waziristan to the mess tables of Rawalpindi and the sectarian madrassas of the Punjab, Hussain portrays a country which was already seething with unrest before political violence claimed its highest profile victim in December 2007. As the author shows, whoever was behind the assassination of Benazir Bhutto, its main effect has been to accelerate the country s fragmentation, creating a level of uncertainty and chaos from which only extremists and terrorists can benefit. Whatever lies in wait for Pakistan Talibanization, civil war or worse it will have grave implications for the entire world.
Include Notes and Index
Keywords: Terrorism--Religious Aspects--Islam -- Terrorism